Optimization of titanium recovery from drinking water treatment plant residue as potential photocatalyst - Zulkapli, Nor Syahidah (2017)
Titanium dioxide (TiO2) is known for its excellent photocatalytic activity and many industries have now shifted their efforts to recover TiO2 from secondary sources. Hydrometallurgy techniques which comprise of leaching, purification and precipitation have been commonly used to recover TiO2. However, this technique involves many processes and further work is needed to improve the laboratory process. This study aims to optimize the titanium leaching from drinking water treatment plant (DWTP) residue using response surface methodology (RSM). The parameters studied were acid concentration, temperature and solid to liquid ratio. The purification work was carried out using solvent extraction and the percentage recovery of titanium using Cyanex 272 and Cyanex 301 were investigated. The final product of TiO2 was obtained via precipitation using magnesium oxide. The performance of TiO2 as photocatalyst was evaluated using methylene blue and fungi under UV light irradiation. From the characterization study, it was found that the DWTP residue was poorly crystalline and predominantly consists of kaolinite and quartz with minor constituent of hematite, illite and anatase. Experimental results showed that a maximum leaching of titanium was obtained at 66% with optimum condition were found to be at 5.5 M acid concentration, 62˚C heating temperature and 10 g/L solid to liquid ratio. In solvent extraction, the best titanium recovery was achieved at 86% using Cyanex 272 with low extraction of aluminium and iron. In contrast, Cyanex 301 showed 60% titanium recovery with 54% of aluminium was extracted into the organic phase. The X-ray Fluorescence (XRF) analysis indicated that 71% of TiO2 was produced. In addition, X-ray Diffraction (XRD) confirmed the formation of TiO2 with the crystalline anatase phase detected at 2θ values of 25.3º, 37.8º, 48.0º. FESEM micrograph of TiO2 showed that the aggregates were present in the form of uniform spherical shape with considerable variation of particle size. The photocatalytic activity of the final product TiO2 under UV light irradiation showed maximum degradation (84%) with 0.5 g/L TiO2 loaded in methylene blue solution. At similar amount of loaded TiO2, the findings indicated that almost 50% of the fungi growth was inhibited within 14 days. Additionally, zero inhibition of fungi growth was observed without the presence of TiO2. In summary, the photocatalyst TiO2 had been successfully recovered from DWTP residue using an optimized leaching process, hence contributes to the improvement of hydrometallurgy technique.